ADSCs labeled with SPIONs tracked in corpus cavernosum of rat and miniature pig by MR imaging and histological examination - Qingqiang Gao; Jianhuai Chen; Wenren Zuo; Bin Wang; Tao Song; Chunlu Xu; Wen Yu; Yutian Dai; Songzhan Gao; Leilei Zhu; Jie Yang (Scientific Reports, 2024)
Abstract Adipose tissue-derived stem cells (ADSCs) have been shown to improve erectile function in animal models of erectile dysfunction. However, few studies have been carried out using a reliable in vivo imaging method to trace transplanted cells in real time, which is necessary for systematic investigation of cell therapy. The study aims to explore the feasibility of non-invasively monitoring intracavernous injection of ADSCs in rat and miniature pig corpus cavernosum using in vivo magnetic resonance (MR) imaging. Thirty-six male Sprague Dawley rats (10 weeks old) and six healthy, sexually mature male miniature pigs (20 kg weight) were obtained. ADSCs were isolated from paratesticular fat of donor rats and cultured. Then ADSCs were labeled with superparamagnetic iron oxide nanoparticles (SPIONs), a type of MR imaging contrast agent, before transplantation into rats and pigs. After intracavernous injection, all rats and pigs underwent and were analyzed by MR imaging at the day of ADSC transplantation and follow-up at 1, 2 and 4 weeks after transplantation. In addition, penile histological examination was performed on all rats and pigs before (n = 6) and at 1 day (n = 6), 1 week (n = 6), 2 weeks (n = 6) or 4 weeks (n = 12) after ADSC transplantation. SPION-labeled ADSCs demonstrated a strong decreased signal intensity compared with distilled water, unlabeled ADSCs or agarose gel. SPION-labeled ADSCs showed a hypointense signal at all concentrations, and the greatest hypointense signal was observed at the concentration of 1 × 106. MR images of the corpus cavernosum showed a hypointense signal located at the injection site. T2*-weighted signal intensity increased over the course of 1 week after ADSCs transplantation, and demonstrated a similar MR signal with that before ADSCs transplantation. After SPION-labeled ADSC injection, T2*-weighted MR imaging clearly demonstrated a marked hypointense signal in pig corpus cavernosum. The T2*-weighted signal faded over time, similar to the MR imaging results in rats. Obvious acute inflammatory exudation was induced by intracavernous injection, and the T2*-weighted signal intensity of these exudation was higher than that of the injection site. The presence of iron was detected by Prussian blue staining, which demonstrated ADSC retention in rat corpus cavernosum. Lack of cellular infiltrations were demonstrated by H&E staining before and 4 weeks after transplantation, which indicated no negative immune response by rats. Prussian blue staining was positive for iron oxide nanoparticles at 2 weeks after transplantation. SPION-labeled ADSCs showed a clear hypointense signal on T2-weight MRI in vitro and in vivo. The MR signal intensity in the corpus cavernosum of the rats and miniature pigs faded and disappeared over time after ADSC transplantation. These findings suggested that MR imaging could trace transplanted ADSCs in the short term in the corpus cavernosum of animals.